Implementation of a therapeutic reconciliation procedure at admission by the emergency department - Elena Urbieta Sanz; Abel Trujilano Ruiz; Celia García-Molina Sáez; Sonia Galicia Puyol; Carmen Caballero Requejo; Pascual Piñera Salmerón (Elsevier, 2014)
Target: To evaluate the results of the implementation of a therapeutic reconciliation procedure (TRP) at admission by the emergency department (ED) Methods: Prospective observational study conducted in the ED of a Referral Hospital Area. We collected the results of the implementation of a TRP from September to December 2012. A pharmacist attended daily to emergency department meeting and reviewed medical history to select those patients with high risk of reconciliation error (RE) according TRP. Afterwards, home medication history was elaborated with emergency department and primary care records and interview with the patient or caregiver. Therapeutic reconciliation took place with the emergency physician, considering RE any discrepancies not justified by the doctor. The potential severity of RE was assessed by emergency physicians outside the study using NCCMERP'S categorization Results: The pharmacist collected an avarage of 1,3±2,2 home medication more than the emergency physician finding 564 discrepancies with the emergency record in 95,8% of the patients. 167 were RE affecting 69 patients (71,9%). Most of the errors were due to omissions of the drugs. Acceptance by emergency physicians of the reconciliation interventions was 73,9%. 58% of the RE were considered clinically relevants. Other interventions were also performed with an acceptance of 97%. Greater compliance with risk criteria, polypharmacy and pluripathology were associated with present RE and prescription of high-risk medications with the need for intervention Conclusions: The application of TRP avoided any error in most of the patients. TRP should extend to all patients at risk who admitted by the ED.